2015
DOI: 10.1016/j.polymdegradstab.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel organo-modifier for thermally-stable polymer-layered silicate nanocomposites

Abstract: A new novel approach for the stabilisation of polymer-clay nanocomposites has been investigated based on reacting chemically an antioxidant function, a hindered phenol moiety, with an organic modifier based on a quaternary ammonium salt. The chemically linked antioxidant-containing organic modifier (AO-OM) was then introduced into natural montmorillonite (MMt) through a cation-exchange reaction resulting in antioxidant-containing organo-modified clay (AO-OM-MMt). The new antioxidant-containing modified clay, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The antioxidant‐organo‐modified clay [(AO)OM‐Mt] was produced (see below) by cation‐exchange reaction between the commercial natural unmodified Mt and an ammonium salt of the antioxidant‐containing organic modifier, named here (AO)OM, synthesized according to procedure reported earlier . Briefly, to produce (AO)OM, a reactive antioxidant molecule (a hindered phenol) was grafted onto a quaternary ammonium salt (2‐hydroxyethyl)oleylmethylbis ammonium chloride, molecular weight of 370.64 g/mol, and formula: C 23 H 48 NO 2 , supplied by Akzo Nobel ® under the trade name ETHOQUAD ® O/12 PG This ammonium salt which was used to produce the (AO)OM product is the same as that present in the commercial Cloisite ® 30B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant‐organo‐modified clay [(AO)OM‐Mt] was produced (see below) by cation‐exchange reaction between the commercial natural unmodified Mt and an ammonium salt of the antioxidant‐containing organic modifier, named here (AO)OM, synthesized according to procedure reported earlier . Briefly, to produce (AO)OM, a reactive antioxidant molecule (a hindered phenol) was grafted onto a quaternary ammonium salt (2‐hydroxyethyl)oleylmethylbis ammonium chloride, molecular weight of 370.64 g/mol, and formula: C 23 H 48 NO 2 , supplied by Akzo Nobel ® under the trade name ETHOQUAD ® O/12 PG This ammonium salt which was used to produce the (AO)OM product is the same as that present in the commercial Cloisite ® 30B.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, to produce (AO)OM, a reactive antioxidant molecule (a hindered phenol) was grafted onto a quaternary ammonium salt (2‐hydroxyethyl)oleylmethylbis ammonium chloride, molecular weight of 370.64 g/mol, and formula: C 23 H 48 NO 2 , supplied by Akzo Nobel ® under the trade name ETHOQUAD ® O/12 PG This ammonium salt which was used to produce the (AO)OM product is the same as that present in the commercial Cloisite ® 30B. As was shown previously, the (AO)OM is a mixture of mono‐ and disubstituted compounds containing one and two Irganox acid molecules, respectively, at a ratio of approximately 2:3.…”
Section: Methodsmentioning
confidence: 99%
“…Flame retardancy of polymeric materials is a subject of major concern due to the need to minimize fire risk and meet fire safety requirements [1], especially for timber structures (plywood, density board, and fiberboard), which are widely used as interiorly decorative materials. Construction materials have long been required to resist burn through or sudden loss of mechanical properties, and maintain structural integrity, whilst continuing to stay intact when exposed to fire or heat [2,3]. Consequently, surface coating with flame retardant paints or varnishes emerges as an available, effective, and efficient surface-treatment method.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, surface coating with flame retardant paints or varnishes emerges as an available, effective, and efficient surface-treatment method. Intumescent flame retardant (IFR) coatings have been employed as ecologically-friendly substitutes for halogen-containing flame retardant additives [4], which favor the formation of shielding char layers, providing adequate fire suppression and/or thermal insulation [2,3], due to their facile, cost-effective, and energy-efficient synthesis. IFR coatings can be used not only for wood fire protection, but also (especially) for thermal insulation protection of steel, which prevents the loss of mechanical properties in case of fires, and allows for more effective evacuation and fire extinguishing [3].…”
Section: Introductionmentioning
confidence: 99%
“…[10] In order to reduce the physical loss of the antioxidants during the processing of the HDPE resin, some hindered phenol antioxidants with different chemical structures were developed, such as macromolecular antioxidants, polymerbound antioxidants, immobilized antioxidant. [11][12][13] Gyorgy Kasza synthesized hyperbranched poly(ethyleneimine) based macromolecular antioxidants with hyperbranched poly(ethyleneimine) as p-substituent of the phenolic hydroxyl and found that these antioxidants had the best stabilizing efficiency in both thermo oxidative and photooxidation in polypropylene films . [14] Cuiqin Li synthesized a series of hyperbranched macromolecule bridged hindered phenol antioxidants using hyperbranched macromolecules as p-substituent of the phenolic hydroxyl and the results of antioxidant activities showed that the antioxidant activities increased with increasing of the alkyl-chain length of psubstituent .…”
mentioning
confidence: 99%